Occupational Dose Estimation with Field Size, Position and C-Arm Gantry Tilt Variations During Interventional Cardiology Procedures - Nurdina Gita Pratiwi; Supriyanto Ardjo Pawiro; Kristina Tri Wigati; Djarwani S. Soejoko (Journal of Medical Physics and Biophysics, 2014)
In Interventional Cardiology, dose received by the patient is relatively higher, while the occupational would receive scattered radiation dose whose quality is relatively lower. However, the occupational received accumulative doses of all cardiovascular procedures were done over the years. Therefore, the purpose of this paper will focus to estimate the distribution of scattered dose to occupational without any protective shielding in the Cath Lab. The scattered dose rate was measured by using survey detector of Unfors Xi. The detector was placed at 6 different positions around the phantom. Each measurement position has eleven points from 25 to 175 cm above the floor with increment of 15 cm as the illustration of partial height of occupational organ. Experimentally a Rando phantom was irradiated by automatic pulsed fluoroscopy with condition varies in the range of 88-93 kV and 5.7-9.4 mA depend on gantry tilt and field size. The Philips C-arm gantry tilt was varied at 0o PA projection, 20o and 30o Caudal, 20o and 30o Cranial, and 40o and 50o Left Anterior Oblique, and also Flat Panel Detector (FPD) was varied at 20 x 20 and 25 x 25 cm2. Generally, the greatest dose rate was known at level corresponding to the waist (100 cm) of occupational and the lowest at head areas (175 cm) of occupational which is 2.49 mGv/h and 0.02 mGy/h, respectively. The given data showed that the scattered fractions are in the range of 0.001-0.060% from its primary dose at isocenter. The scattered doses tend to increase with gantry tilt for all positions. Increasing field size of FPD will decreased the scattered fraction from its dose at isocenter, and also it affects the scattered dose rate.